The Effect of wall on subsonic non-circular jets (International Journal of Scientific Research and Management (IJSRM), 2018)
The present experimental study aims at characterizing the mixing characteristics of subsonic elliptic and rectangular orifice jets (Ve = 51 m/s) in the presence of wall of different surface roughness, namely smooth, fine and coarse, placed parallel to the jet axis at the edge of the orifice exit. The wall of length 120 cm of different surface roughness was oriented either parallel to the minor axis plane or major axis plane if the orifice. The wall had a strong effect on the mixing characteristics of elliptic and rectangular jets. The centerline velocity measurement showed that the potential core of elliptic and rectangular orifice jets was around 3De and 3.5De. For both jets, all the wall configurations retarded the mixing of jet with the ambient fluid only in the characteristic decay zone but not in the core and fully developed zones. The level of mixing retardation was found to be maximum when wall was placed parallel to the major axis plane of the jet. The effect of wall on jet mixing was intense for rectangular jet compared to elliptic jet.